Longterm Impact of Living Liver Donation: A Self‐Report of the Donation Experience. Issue 5 (26th March 2019) - LaPointe Rudow, Dianne; DeLair, Samantha; Feeley, Thomas; Florman, Sander; Guarrera, James; Kinkhabwala, Milan; Orloff, Mark; Teperman, Lewis; Morgan, Glyn
Abstract : Outcomes for adult‐to‐adult living liver donors (LDs) are largely based on short‐term data drawn from single‐center studies. The aim of this study was to determine how living liver donation (LLD) impacts self‐reported quality‐of‐life (QOL) up to 6 years after donation in a sample of residents from New York State. New York transplant programs are state‐mandated to track LDs as part of a quality assurance and patient safety effort. Donor‐reported QOL within 1 year of donation and longitudinal data over a 10‐year period were analyzed. Self‐reported surveys include the following domains: employment, finances, health/life insurance, activities of daily living, physical/emotional health, donor experience, relationships, and LD opinions. There were 220 LDs in New York (2004‐2013) who completed a survey over the 10‐year period with many donors completing surveys at several points in time. Overall, longterm LDs remain as comfortable about LLD as they were during the first year after donation (95%). The majority of LDs reported feeling as well as before LLD (72%). At 1 year after donation, 60% of subjects self‐reported medical problems, and 30% reported emotional issues. However, the majority reported that they would willingly donate again. In conclusion, LDs remain satisfied with their decision to donate over time. A minority of LDs report longterm medical and emotional issues. The conclusions provide information for educational interventions to improve informed choice to those considering donation.